Influence of carrier agents on nutritional, chemical, and antioxidant profiles of fruit juices during drying processes: a comprehensive review - Rahul Pujapanda; Hamid; Omar Bashir; Rafeeya Shams; Kshirod Kumar Dash; Gulden Goksen; Ayaz Mukarram Shaikh; Kovács Béla (Discover Food)
Abstract Fruit powders are a promising alternative to fresh fruits and juices due to high perishability, offering several advantages such as longer shelf life, reduced weight and volume, and wide opportunity for processing into various value-added products. This review explores the bioactive aspects of major fruits like mango, pineapple, pomegranate, orange, grape, guava, litchi, blackberry, and aonla, which can be preserved by the use of appropriate carrier material and drying methods. Direct drying of fruit pulps and juices leads to nutritional component degradation, which can be prevented by adding a carrier material. Carrier agents like Maltodextrin, Gum Arabic, and Modified Starch contribute to the volume and stability of fruit powders, improve their solubility and texture, and enhance their flow properties and dispersibility. Carrier agents with suitable drying methods like spray drying or freeze drying are essential in food powder formulation because it can function as vehicles to improve texture, stability, solubility, and shelf life. Carrier substances improve the solubility of components, facilitating the dissolution of the powder in liquids and preserving the volatile flavorings, natural color, nutritional properties, and techno-functional properties of the obtained powder. This also increases its flow properties, reducing stickiness and clumping, preventing the formation of clusters, and prolonging the duration of storage, which is especially crucial for their application in instant beverage mixes, the bakery industry, and powdered dietary supplements. In this way, different carriers add bulk to the powder, aiding in attaining the desired volume and consistency. Their distinct capabilities render them indispensable components in a diverse array of powdered food items, contributing to the overall quality of the finished product. In general, the utilization of carrier agents throughout the drying process aids in maintaining the nutritional and sensory characteristics of food products, ensuring that they retain their desirable attributes from the time they are produced until they are consumed.